Women's Human Rights and Migration : Sex-Selective Abortion Laws in the United States and India - Kalantry, Sital (Pennsylvania studies in human rights., 2017)
In Women's Human Rights and Migration, Sital Kalantry examines the laws to ban sex-selective abortion in the United States and India to argue for a transnational feminist legal approach to evaluating prohibitions on the practices of immigrant women that raise human rights concerns.